2021
DOI: 10.1007/s00068-021-01801-1
|View full text |Cite
|
Sign up to set email alerts
|

Internal fixation versus hip arthroplasty in patients with nondisplaced femoral neck fractures: short-term results from a geriatric trauma registry

Abstract: Purpose To determine whether internal fixation (IF) or hip arthroplasty (HA) is associated with superior outcomes in geriatric nondisplaced femoral neck fracture (FNF) patients. Methods Data from the Registry for Geriatric Trauma of the German Trauma Society (ATR-DGU) were analyzed (IF Group 449 and HA Group 1278 patients). In-hospital care and a 120-day postoperative follow-up were conducted. Primary outcomes, including mobility, residential status, reope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
1
1
Order By: Relevance
“…IF is a hip-preserving method, thus one could theorize that the fracture may not have fully healed 4 months after surgery. However, both our study and a recent study by Laubach et al show that, compared with HA (but not THA), IF patients recover as well or better in terms of mobility even within 4 months ( 12 ). 2 recent review studies reported no clinical benefits of THA compared with HA when adjusting for confounders ( 13 , 14 ).…”
Section: Discussioncontrasting
confidence: 60%
“…IF is a hip-preserving method, thus one could theorize that the fracture may not have fully healed 4 months after surgery. However, both our study and a recent study by Laubach et al show that, compared with HA (but not THA), IF patients recover as well or better in terms of mobility even within 4 months ( 12 ). 2 recent review studies reported no clinical benefits of THA compared with HA when adjusting for confounders ( 13 , 14 ).…”
Section: Discussioncontrasting
confidence: 60%
“…46 Several other studies also showed lack of statistical significance when comparing internal fixation and arthroplasty in the domain of mortality (Table 2). [47][48][49][50] Most of the comparative studies to date, however, do not report a reliable method of measuring functional outcomes, if at all. Functional capabilities of patients postoperatively can have profound impacts on their quality of life and, subsequently, morbidity and mortality.…”
mentioning
confidence: 99%